Pengaruh Perputaran Kas, Perputaran Piutang, Perputaran Persediaan Dan Perputaran Total Aktiva Terhadap Profitabilitas Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Dibursa Efek Indonesia (BED Periode 2009-2013. - Benida Sari; Erna Listianingsih; Lestari Wuryanti (Universitas Malahayati, 2015)
Abstract, This study aims to determine whether there is influence of cash tumover, receivabletumover, inventory turnover and total asset turnover to profitability (Return On Investment) inCompany Manufacturing Sector of Basic Industry and Chemical Listed Securities Indonesia StockExchange (BEI) Period 2009-2013. This study used secondary data obtained from www.bci.co.id2015. Data analysis method used is the test data normality, classic assumption test and further testingof hypotheses. The results showed that partially (t test) cash turnover partially influence onprofitability (ROT), partially receivable tumover affect the profitability (ROI), inventory turnover ispartially no effect on profitability (ROD), total asset turnover partially influence to Profitability (ROD,the Sector Manufacturing Company and Chemical Industry Association of Registered SecuritiesIndonesia Stock Exchange (BEI) Period 2009-2013. Simultaneously cash tumover, perpuatranreceivable, inventory turnover and total asset tumover together (Test F) affects peofitabilitas (ROD ona firm base and chemical industry sectors listed on the Indonesia Stock Exchange (BEI).